Facultative predation expands the ecological repertoire of Streptomyces - Yamada, Keith; Koroleva, Arina; Tirkkonen, Heli; Siitonen, Vilja; Laughlin, Mitchell; Moglia, Amanda; Matroodi, Soheila; Akhgari, Amir; Mazurier, Guillaume; Niemi, Jarmo; Metsä-Ketelä, Mikko (American Society for Microbiology, 2026)
Microbial predators obtain energy from killing other living cells. Streptomyces are soil bacteria that are known to produce numerous catabolic enzymes and antimicrobial compounds to defend against competing organisms. Here, we demonstrate that Streptomyces are predatory bacteria that prey on Saccharomyces cerevisiae. Time-lapse fluorescence microscopy and scanning electron microscopy revealed that predation is initiated by physical contact between Streptomyces lavendulae YAKB-15 and yeast cells. Comparative transcriptomics indicated that the interaction triggered the production of numerous extracellular catabolic enzymes and natural products, while delaying morphological development. Proteomics and enzyme assays confirmed co-culture-dependent production of carbohydrate-active enzymes (CAZymes), including various glucanases, mannosidases, and chitinases, which degraded the yeast cell wall. Streptomyces lavendulae YAKB-15 destabilized yeast cell membranes through the production of two polyene antifungal agents, pentamycin and filipin III. We found that the bioactivity was enhanced by cell-associated cholesterol oxidase ChoD, putatively by modulating sterol extraction kinetics. Metabolomic analyses suggest Streptomyces assimilates yeast cell sterols as nutrients. Furthermore, we observed the depletion of yeast-derived phosphatidylcholine and phosphatidylethanolamine lipids, which points to their consumption. We show that yeast predation is a common phenomenon in Streptomyces, which changes the paradigm of how these bacteria should be considered in the soil microbiome ecosystem.IMPORTANCESoil is a rich environment for microbes, where they compete for space and resources. Streptomyces bacteria are well known for their ability to synthesize natural products, particularly antibiotics, that are used in chemical defense against competing microbes. Here, we show that Streptomyces are, in fact, predatory bacteria. Upon encountering yeast cells, Streptomyces initiate the production of numerous enzymes that digest the cell wall and cell membrane. In addition, the interaction triggers the production of natural products that destabilize the yeast cell membrane. Collectively, these actions lead to the death of yeast cells and release of cellular building blocks that Streptomyces can use as nutrients. The work fundamentally shifts the paradigm of how Streptomyces are perceived within the soil microbiome ecosystem.
Keywords: Streptomyces; catabolic enzymes; polyenes; predation; yeast.